(untitled) (Research, Society and Development, 2024)
Objective: Identify the main factors associated with the occurrence of DRPI. Methodology: Integrative Literature Review based on the guiding question: What are the factors associated with the occurrence of DRPI in hospital environments and what are the most common medical devices related to PI? The time frame was between the years 2013 and 2023 and the databases consulted were: Scielo, MEDLINE, Lilacs and Scopus using the descriptors: “Pressure Injury”, “Equipment and Supplements’’, “Triggering Factors”, “Hospital” and its correspondents in English and Spanish. Results: The study sample included 16 articles published between 2016 and 2023, with a predominance in 2021. The analysis of the articles provided information about the medical devices involved and triggering factors for these injuries, in which four categories were defined: factors related to the devices, to the individual, to preventive care and to nursing care. Factors such as pressure, microclimate, pH and type/size of devices contribute to these injuries and require preventive measures such as constant monitoring and appropriate repositioning. Medical devices, such as NIV masks and endotracheal tubes, are identified as main causes. Conclusion: Addressing factors associated with LPRDM is essential to prevent and improve the management of these injuries and promote a safer hospital environment. Furthermore, it is crucial to involve the entire multidisciplinary team in management to avoid underreporting and undertreatment. A limitation of the study was the restrictions of "Never Events" by ANVISA, which restrict the notification of less serious cases and affect the quality of care.